Changes in the Major Antioxidant Compounds of Red Cabbage Under Water Stress Applied at Different Vegetative Growth Periods - Okan Erken; Umut Mucan; Bayram Kızılkaya; Murat Yıldırım (Journal of Agricultural Sciences)
Effective and efficient use of water resources has become an important issue in recent studies, where the impacts of climate change has become more apparent and alternative solutions are discussed. There, however, are limited studies that look at the impacts of water stress at different vegetative periods. For this reason, in this study, different levels of water treatment (0%, 30%, 70%) were applied to red cabbage at two stages of development (early and late vegetative) in a two-year field study. The effect of water stress on the major antioxidant compounds, as well as on yield and some morphological parameters were investigated.According to the findings, the least yield loss (22%) occurred in the early vegetative period of the second-year trial where 70% irrigation water was applied, while the highest yield loss (56%) was obtained during the early vegetative period of the first-year trial where no irrigation was applied. Biochemical analyses revealed that the highest accumulation of flavonoids, 0.83 mg g-1, and anthocyanins, 1.51 mg g-1, occurred in the early vegetative period with the trial that received no irrigation treatment. The phenolic compound content was determined as 1.62 mg g-1, and the antioxidant capacity was found to be 1.93 mg g-1 during the late vegetative period in the trials without irrigation treatment. These findings suggest that in regions with limited water resources, water conservation can be practiced during different vegetative periods in order to get higher biochemical benefits with a lower yield loss when cultivating red cabbage.